2020
DOI: 10.1177/0896860819879891
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre registry data analysis comparing outcomes of culture-negative peritonitis and different subtypes of culture-positive peritonitis in peritoneal dialysis patients

Abstract: Background: The outcomes of culture-negative peritonitis in peritoneal dialysis (PD) patients have been reported to be superior to those of culture-positive peritonitis. The current study aimed to examine whether this observation also applied to different subtypes of culture-positive peritonitis. Methods: This multicentre registry study included all episodes of peritonitis in adult PD patients in Australia between 2004 and 2014. The primary outcome was medical cure. Secondary outcomes were catheter removal, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…More importantly, our results were further confirmed by using a multivariable logistic regression model. Our observation had both similarities and differences with previous data from ANZDATA registry study, which included 11122 episodes of peritonitis in 5367 patients in Australia during the period of 2004-2014[ 29 ]. Our study demonstrated that the complete cure rates were comparable between DM group and non-DM group, which was similar to the study by Htay et al[ 29 ].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…More importantly, our results were further confirmed by using a multivariable logistic regression model. Our observation had both similarities and differences with previous data from ANZDATA registry study, which included 11122 episodes of peritonitis in 5367 patients in Australia during the period of 2004-2014[ 29 ]. Our study demonstrated that the complete cure rates were comparable between DM group and non-DM group, which was similar to the study by Htay et al[ 29 ].…”
Section: Discussionsupporting
confidence: 76%
“…DM was not associated with PDAP-related death in our study. In contrast, Htay et al[ 29 ] showed that DM correlated with PDAP-related death. Regional differences may account for this discrepancy.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, patients in the EOP group might be suffered from PDAP due to unskilled operation, and Staphylococcus epidermidis was the main pathogenic agents caused by touch contamination [29, 30]. Meanwhile, as Htay et al [31] reported, most patients with the culture‐negative peritonitis respond well to treatment, which was similar as non‐Staphylococcal aureus gram‐positive organisms. Therefore, we speculated that non‐Staphylococcal aureus gram‐positive organisms, especially Staphylococcus epidermidis with good therapeutic effect, may be one of the main culprits of culture‐negative PDAP.…”
Section: Discussionmentioning
confidence: 99%
“…These results, as well as those of previous studies, indicate favorable outcomes, a high cure rate (77–80%), and a low catheter removal rate (8–12%) in patients with culture-negative peritonitis. 4 , 8 , 9 Although median time to primary response was shorter and the probability of primary response was higher in the combination therapy group, the final clinical outcomes, primary response at day 5, and incidence of relapse peritonitis did not differ significantly between the two groups. The fact that the short-term outcomes are quite similar in the two groups suggests that the benefits combination of cefazolin and ceftazidime may not be clinically meaningful in terms of primary response at day 5 and in relapse peritonitis.…”
Section: Discussionmentioning
confidence: 89%